Evaluation of national food and nutrition policy in Albania - Mersini Ehadu; Hyska Jolanda; Burazeri Genc (Sciendo, 2017)
The paper aims to describe the progress that has been made in the implementation of the Albanian food and nutrition policy since 2003, so as to consider its impacts to date, and to identify strategic priorities/critical areas and priorities for Albania's future policy on improving the national food and nutrition situation.